STRATEGI PERSONAL BRANDING MAX5 OLEH STAR MEDIA NUSANTARA MELALUI MEDIA FACEBOOK - Suraya Suraya (Konvergensi, 2015)
The purpose of this paper is to know about Star Media Nusantara Public Relations Strategy to do Personal Brandingof Max5 with Facebook. This research using a qualitative approach as a research methodology , this study using descriptive case studies . Results of the study : Star Media Nusantara used Facebook for PR Strategy in Personal Branding Max5. This activity phase about Phase I: Formative Research (analyzing the situation, analyzing the organization, analyzing the publics) Phase II: Strategy (establishing goals dan objectives, formulating action and response strategies, using effective communication) Phase III: Tactics (choosing communication tactics, implementing the strategic plan to used facebook for relationship Max5 with They Fans) Phase IV: Evaluative Research (evaluating the strategic plan). PR Strategy and tactic to doing with facebook because the information can be share and get in anywere and every where. Conclusion : Star Media Nusantara used PR strategy in personal branding of Max5 with facebook in another way, such as to share Max activity, picture and video. This is how to make a personal branding in society mind and how to buid relationship between Max5 and they fans. Suggest : We hope Star Media Nusantara make more strong a positioning statement for Max5 if they look in picture.Key words :Public Relations Strategy, Personal Branding, Facebook, Max5